(untitled) (Italian Journal of Public Health, 2007)
Objective: This research aims to: a) assess the energy expenditure during typical forestry activities; b) assess the actual workload of forestry work; c) define the eventual relationship between oxygen uptake ( ) and heart rate during the studied working phases. Methods: Eleven healthy skilled forestry workers were studied. Using a portable device, oxygen uptake ( ), carbon dioxide output ( ), pulmonary ventilation ( ) and heart rate (HR) were measured. The forestry work was divided into four phases: walking uphill, felling, limbing & chain-sawing and complementary activities. A work time report was kept and in each phase a weighted average (WA) of all parameters was obtained. Results:Walking uphill, felling, limbing & chain-sawing activities did not show significant statistical differences between each other and were classified as heavy activities (mean 2.17 lmin-1,mean HR 157 beatmin-1). The complementary activity was found to be less demanding and statistically differed in respect to the others ( 0.55 l min-1, HR 98 beat min-1). By theWA, the actual workload of forestry work resulted in a moderate to heavyoptimal job ( and HR being 1.51 l min-1 and 133.5 beat min-1 respectively in a typical working day). Furthermore it was possible to set up a relationship between and HR for the forestry work. Conclusions: Forestry activity can be classified as moderate to heavy-optimal. Finally, a good and linear correlation between and HR proved to be an easy tool to evaluate the metabolic demand.